2014
DOI: 10.1039/c4ra00332b
|View full text |Cite
|
Sign up to set email alerts
|

Alternative synthesis of the anti-baldness compound RU58841

Abstract: A bromine-nitro substitution at tertiary carbon and using 2-nitropropane as leaving group enable a short phosgene-free synthesis of RU58841.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In Tables , we listed all published α‐amino acid derivatives and (either linear or, more rarely, cyclic) peptides to the decamer level where single or consecutive fully‐extended (C 5 ) structures were identified by X‐ray diffraction in the last 5/6 years. A few, still unpublished 3D‐structures, characterized by the C 5 form and solved in the Padova laboratory, are presented in Table…”
Section: Detailed Literature Survey On Peptides Since 2012mentioning
confidence: 99%
“…In Tables , we listed all published α‐amino acid derivatives and (either linear or, more rarely, cyclic) peptides to the decamer level where single or consecutive fully‐extended (C 5 ) structures were identified by X‐ray diffraction in the last 5/6 years. A few, still unpublished 3D‐structures, characterized by the C 5 form and solved in the Padova laboratory, are presented in Table…”
Section: Detailed Literature Survey On Peptides Since 2012mentioning
confidence: 99%
“…This compound has been previously reported. 21 1-Methyl-3-phenylhydantoin 9g. Yield: 54% (207 mg, 1.09 mmol).…”
mentioning
confidence: 99%
“…However, we have found that the Kornblum substitution does proceed on a tertiary centre that is alpha to an anilide carbonyl group. We have hence used the Kornblum substitution to prepare an α-nitroisobutyranilide (2) in order to perform an alternative synthesis of the hydantoin anti-baldness compound RU58841, a process that we published in 2014 [10]. The reaction was simple and performed in high yield with low cost materials (Figure 3).…”
Section: Figure 2 the Kornblum Substitutionmentioning
confidence: 99%
“…(1). Characterization data for 1 are provided in our 2014 publication [10] where it is given the correct IUPAC name of "2-Bromo-N- [4-cyano-3-(trifluoromethyl)phenyl]-2-methylpro panamide".…”
Section: Acylation Reactionsmentioning
confidence: 99%